2015
DOI: 10.4314/gjds.v12i1-2.6
|View full text |Cite
|
Sign up to set email alerts
|

Towards Universal Health Coverage: Exploring the Determinants of Household Enrolment into National Health Insurance in the Kassena Nankana District, Ghana

Abstract: This study investigates the determinants of household participation in National HealthInsurance Scheme (NHIS) in the Kassena-Nankana District

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 27 publications
2
38
1
Order By: Relevance
“…The inability of these households to renew their subscription is attributed to varying factors at both health systems and individual levels. For instance, proximate factors such as unemployment [27], low level of income [28][29][30], limited education [27][28][29]31], and individual's role within their families [27] discourage households from enrolling into the scheme. This apparently suggests that the health systems and sociodemographic factors of some households limit them from enrolling into the NHIS subscription, thereby preventing UHC.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The inability of these households to renew their subscription is attributed to varying factors at both health systems and individual levels. For instance, proximate factors such as unemployment [27], low level of income [28][29][30], limited education [27][28][29]31], and individual's role within their families [27] discourage households from enrolling into the scheme. This apparently suggests that the health systems and sociodemographic factors of some households limit them from enrolling into the NHIS subscription, thereby preventing UHC.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are mostly related to the social, economic, demographic, and health status of households [27][28][29][30][31][32][33][34][35][36]. Across different regional and geographic boundaries, social factor such as gender influences NHIS policy enrolment [27,28,30,32,34]. Past studies, for instance, have showed that females have more propensities to enrol and renew their NHIS policy compared with males [30,31,33].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations